Diagnostic Significance of Downregulated circMORC3 as a Molecular Biomarker of Hypopharyngeal Squamous Cell Carcinoma: A Pilot Study - Guo Y; Huang Q; Zheng J; Hsueh CY; Huang J; Yuan X; Chen H; Zhou L (Cancer Management and Research, 2020)
Yang Guo, Qiang Huang, Juan Zheng, Chi-Yao Hsueh, Jiameng Huang, Xiaohui Yuan, Hui Chen, Liang Zhou Department of Otorhinolaryngology Head and Neck Surgery, Shanghai Key Clinical Disciplines of Otorhinolaryngology, Eye and ENT Hospital of Fudan University, Shanghai, People’s Republic of ChinaCorrespondence: Hui Chen; Liang ZhouDepartment of Otorhinolaryngology Head and Neck Surgery, Shanghai Key Clinical Disciplines of Otorhinolaryngology, Eye and ENT Hospital of Fudan University, No 83, Fenyang Road, Xuhui District, Shanghai 200031, People’s Republic of ChinaFax +86 21 6437 7134Email chenhuizhen@hotmail.com; zhoulent@126.comBackground: Circular RNAs (circRNAs) have proven to be of great clinical significance as diagnostic biomarkers in various cancers. Here, we investigate the expression of circMORC3 in hypopharyngeal squamous cell carcinoma (HSCC), exploring whether it could serve as a diagnostic marker of HSCC.Methods: CircMORC3 expression levels were detected in HSCC tissues and adjacent normal tissues using quantitative real-time polymerase chain reaction (qRT-PCR). The relationships between circMORC3 expression levels and clinicopathologic factors were explored. CircMORC3 expression levels in plasma from HSCC patients and non-tumor patients were also detected by qRT-PCR. Finally, receiver operating characteristic (ROC) curves were established to evaluate the diagnostic value of circMORC3 as a potential HSCC biomarker in tissues and plasma.Results: The expression levels of circMORC3 were significantly lower in HSCC tissues than paired adjacent normal tissues, and the area under the ROC curve was 0.834. The decreased expression of circMORC3 was correlated to T stages and tumor sizes. Similarly, the circMORC3 expression levels in HSCC patient plasma were lower than non-tumor patient plasma, and the area under the ROC curve was 0.767.Conclusion: Our results indicate that circMORC3 was downregulated in HSCC tissues and plasma, and it could serve as an early diagnostic HSCC biomarker.Keywords: circMORC3, diagnostic significance, molecular biomarker, hypopharyngeal squamous cell carcinoma